Early detection of myocardial dysfunction using two-dimensional speckle tracking echocardiography in a young cat with hypertrophic cardiomyopathy - Suzuki, Ryohei (JFMS Open Rep, 2018)
CASE SUMMARY: A 5-month-old intact female Scottish Fold cat was presented for cardiac evaluation. Careful auscultation detected a slight systolic murmur (Levine I/VI). The findings of electrocardiography, thoracic radiography, non-invasive blood pressure measurements and conventional echocardiographic studies were unremarkable. However, two-dimensional speckle tracking echocardiography revealed abnormalities in myocardial deformations, including decreased early-to-late diastolic strain rate ratios in longitudinal, radial and circumferential directions, and deteriorated segmental systolic longitudinal strain. At the follow-up examinations, the cat exhibited echocardiographic left ventricular hypertrophy and was diagnosed with hypertrophic cardiomyopathy using conventional echocardiography. RELEVANCE AND NOVEL INFORMATION: This is the first report on the use of two-dimensional speckle tracking echocardiography for the early detection of myocardial dysfunction in a cat with hypertrophic cardiomyopathy; the myocardial dysfunction was detected before the development of hypertrophy. The findings from this case suggest that two-dimensional speckle tracking echocardiography can be useful for myocardial assessment when conventional echocardiographic and Doppler findings are ambiguous.